2020
DOI: 10.4102/sajems.v23i1.3579
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cognitive dimensions on memorable experiences within a marine tourism context

Abstract: Background: Consumers are increasingly demanding memorable experiences, thereby placing pressure on businesses to meet these demands. The provision of memorable experiences is particularly important to the tourism industry as its core business is to provide experiences. To stage these experiences, businesses must know which dimensions to include. For this purpose, cognitive dimensions present a reasonable starting point.Aim: The current research aimed to explain and examine the cognitive dimensions that have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The studies described above reinforce the assertion that MPAs are an important component of coastal and marine tourism (van der Merwe et al 2011;Jonas et al 2020). In addition to positive economic impacts, MPAs offer a range of recreational opportunities, meeting the needs of both local and international visitors.…”
Section: Positive Effectssupporting
confidence: 76%
“…The studies described above reinforce the assertion that MPAs are an important component of coastal and marine tourism (van der Merwe et al 2011;Jonas et al 2020). In addition to positive economic impacts, MPAs offer a range of recreational opportunities, meeting the needs of both local and international visitors.…”
Section: Positive Effectssupporting
confidence: 76%
“…Qiu [ 46 ] gives the promotion strategy of tourism cultural and creative products in the era of Internet+. Research has shown that understanding the cognitive dimensions of the marine tourism experience will result in a more memorable experience for the tourists and may lead to post-purchase behaviors such as repeat purchases and word-of-mouth referrals, which in turn will increase the commercial interests [ 47 ]. Li and Yu [ 48 ] take Zhuhai marine tourism as the research object to quantify and optimize the influencing factors of marine tourism economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meaningfulness can be defined as "engagement in personally significant activities" (Chandralal and Valenzuela, 2013, p. 293). A tourism experience is more than just observing new sights or visiting new places; it is an inner journey of personal growth and self-development (Jonas et al, 2020). Many activities, such as closeness to nature, enjoyment of the scenery, spiritual explorations or travel, contribute to restoring equilibrium (Hu et al, 2018;Rejikumar et al, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%